17TH-CENTURY OTTOMAN SCHOLARS OF KALAM AND THEIR INTERNAL DISPUTES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article explores the development of the science of kalam (Islamic theology) during the 17th century in the Ottoman Empire. It examines disputes among scholars on certain theological issues, the emergence of deviant groups such as pseudo-Salafis and Jabriyya, and the early signs of their influence.